Effects of Malaysian secondary schools mathematics teachers' familiarity with TIMSS on students' achievement in mathematics - Lessani, Abdolreza; Md Yunus, Aida Suraya; Ahmad Tarmiz, Rohani; Mahmud, Rosnaini (Contemporary Research Center (CRC Publications), 2014)
Many nations nowadays take international comparisons of students’ achievements to assess their success in education. In the mathematics context, Trends in International Mathematics and Science Study (TIMSS) is a well-recognized intentional comparative study that is being carried out to offer insight into students’ achievement and to evaluate a country’s own mathematics education system and practice. The review of TIMSS report, particularly for the eighth-grade level in 2003, 2007 and 2011 shows that although Malaysia has gotten ranking around more than international average in the mathematics achievement, however, its ranking has usually been lower than leading South-East Asian countries such as Hong Kong, Singapore and Japan. The present study proposes that the lack familiarity with the TIMSS content domains including Number, Algebra Geometry, and Data & chance (Statistics & Probability) among Malaysian secondary school mathematics teachers can be an important reason for such a lack of mathematics achievement in Malaysia. We conducted several interviews with the teachers to address this issue and concluded that when the familiarity of a teacher with TIMSS increases, he/she may introduces mathematics concepts to students, from the TIMSS content domains, which do not exist in the Malaysian mathematics textbooks content.